Pelatihan pembuatan proposal Penelitian Tindakan Kelas bagi guru Sekolah Dasar Inpres Sero Kabupaten Gowa - Sudding Sudding; Muhammad Danial; Muhammad Anwar (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
The training on making classroom action research proposal for teachers of SD Inpres Sero Gowa Regency aims tomake participants understand the principles and technical steps of implementing CAR, understand the format and components ofCAR proposal and assessment instruments in the implementation of CAR, and be skilled at preparing CAR proposal andassessment instrument that can be a guideline for teachers in conducting classroom action research in schools. The methodapplied in the implementation of this training is by applying the method of exposure or varied lectures, question and answer,discussion, and practice for approximately 8 hours on the first day. On the second day for approximately 8 hours focused onparticipants preparing proposals and PTK instruments in a guided manner. Then proceed as an independent assignment outsidethe classroom for 4 days. The results obtained after the training were obtained by a product of a proposal text and assessmentinstrument that could be used as a guide (example) for teachers in implementing CAR in schools. From the results of thequestionnaire participants found that 81.3% felt that training was very good, the remaining 18.7% stated that the training wasgood.